Bank lending to emerging markets: Crossing the border - David Lubin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper has two aims. The first is to provide some explanation for the extraordinary collapse in cross-border bank lending to developing countries which has taken place since 1997. The second is to argue that it might be too simplistic to characterize banks' behaviour in the past few years as a pure withdrawal from emerging markets. Instead, it is more appropriate to think of banks as being engaged in a redistribution of their emerging markets' portfolios, from crossborder lending – the traditional form of banks' engagement with developing countries – to incountry lending. In effect, it makes sense to think of banks as `crossing the border' in order to substitute onshore for offshore exposure. Obviously, the questions that arises from this are a) whether such behaviour could make emerging markets financial crises any less likely to happen; and b) whether crises would be any less severe if and when they do happen. The tentative conclusion is that this process of `crossing the border' could prove to be a reliable way for developing countries to reduce their vulnerability to crisis. The critical caveat to this, however, is the recent experience of international banks operating in Argentina. While it is still far too early to draw any conclusions, one dangerous possibility is that banks experience some kind of `revulsion' at the idea of owning domestic balance sheets in developing countries. Should that be the case, the consequences could be grim for developing world, which would have to suffer not only the large collapse of cross-border lending, but also the consequences of falling direct investment in their financial sectors.
Keywords: F32; F34; F21; 330; developing countries; bank lending; foreign direct investment; Argentina; Kreditgeschäft; International; Portfolio-Investition; Entwicklungsländer